Digitalization in Supply Chain Management - Syed, Hunzalah Nafees; Jirsák, Petr; Rathouský, Bedřich; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis explores the potential of blockchain technology in transforming pharmaceutical supply chain management, with a focus on Karachi Pakistan-based pharmaceutical enterprises. Driven by technological advancements and globalization, the pharmaceutical sector faces unique challenges in managing its supply chains, including product authenticity, regulatory compliance, and managing complex distributor networks. Blockchain offers a decentralized, transparent, and immutable ledger system, providing enhanced traceability, efficiency, and risk reduction, which are critical in the pharmaceutical industry. This research investigates the advantages, challenges, and practical implementation of blockchain technology in Karachi's pharmaceutical supply chains, addressing issues such as counterfeit drugs and inefficiencies in conventional supply chain practices. Through qualitative interviews with professionals from both large multinational and small-to-medium pharmaceutical companies in Karachi, this study assesses how blockchain could improve supply chain processes, its barriers to adoption, and its impact on business operations. The findings provide insights into block chain’s role in increasing supply chain transparency, improving compliance, and reducing operational inefficiencies in the pharmaceutical sector.
Vedoucí práce: Petr Jirsák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses